MODEL KECELAKAAN SEPEDA MOTOR PADA RUAS JALAN DENGAN MENGGUNAKAN PENDEKATAN GLM - Sobri Abusini; Harnen Sulistio; Achmad Wicaksono (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2010)
In this study, traffic accidents occurred on roads in Batu, East Java, were observed. Based on these traffic accident data, a model was built to relate the number of motorcycle accidents with the availability of road shoulders, traffic flow, and traffic speed. The results indicate that the availability of road shoulders potentially reduce the number of motorcycle accidents. Conversely, increasing the speed and traffic flow potentially increase the number of motorcycle traffic accidents on the roads in Batu.Keywords: motorcycle accidents, road shoulders, traffic flow, traffic speed